Hubungan Antara Interaksi Teman Sebaya Dan Konsep Diri Dengan Kedisiplinan Siswa - Bumi, Deking Jangkar, Taufik Kasturi, M.Si., Ph.D (2017)
This study objective were knowing: 1) The association between peer interaction and self concept with student discipline; 2) The effective contribution of peer interactions dan concept yourself to the student discipline; 3) The level of peer interaction, self concept and student discipline. This study subjects were students of grade XI of SMK MUHAMMADIYAH 1 Sukoharjo consisting of three classes total of 91 students. Data collection using peer interaction scale, self concept scale and student discipline scale. Data analysis technique using the two predictors regression. Conclusion of the study suggests 1) There is a highly significant relationship between peer interaction and self concept with student discipline. 2) There is a highly significant negative relationship between the peer interaction and the student discipline. 3) There is a highly significant positive relationship between the self concept and the student discipline. The higher the self concept then the higher the student discipline